Novice Writers and Scholarly Publication: Authors, Mentors, Gatekeepers. Pejman Habibie & Ken Hyland (eds.) London: Palgrave Macmillan, 2019. 297 pages. ISBN: 978- 3-319-95332-8 - Jingjing Wang (Ibérica, 2019)
.